Implementasi Program Duta Hatiku dalam Pelayanan Administrasi Kependudukan bagi Penduduk Rentan di Kabupaten Sidoarjo - Yasah, Aulya Dista; Tukiman, Tukiman (Universitas Medan Area, 2025)
This article examines the implementation of the Duta Hatiku Program (Dukcapil Tanggap Bencana Harapan Timbul Kembali Utuh) at the Population and Civil Registration Office of Sidoarjo Regency. The problem focuses on implementing the program in providing easy access to population documents for administratively vulnerable populations. To analyze this problem, the theoretical reference from Van Meter and Van Horn (1975) is used, which includes policy standards and targets, resources, communication between organizations and activity implementers, characteristics of implementing organizations, attitudes of implementers, and social, economic, and political environmental conditions. Data were obtained through interviews, observations, and documentation, then analyzed using a qualitative approach. The research findings show that the Duta Hatiku Program is quite effective in providing easy access to population documents, as evidenced by the printing of 82 population documents in 2023 and increasing to 109 documents in 2024. Although there is an information constraint related to the location or coordinates of disaster sites, such as fire, which are usually not specifically explained by BPBD and cause delays in verification, these can be overcome through coordination with village and sub-district officials.